Effects of black raspberry, blueberry, and blackberry volatile extracts on intestinal barrier dysfunction and inflammation in a Caco-2/RAW264.7 cells co-culture model - Inah Gu; Cindi Brownmiller; Luke Howard; Sun-Ok Lee (Journal of Functional Foods, 2024)
Berry volatiles are responsible for the aroma of berries. However, their impacts on intestinal inflammation are unclear. Thus, this study investigated the effects of black raspberry, blueberry, and blackberry volatile extracts (BVEs) on intestinal barrier dysfunction and inflammation using a Caco-2/RAW264.7 cells co-culture model. BVE treatments significantly enhanced integrity and decreased permeability in LPS-damaged epithelial monolayers with increased tight junctions. Blueberry and blackberry volatile extract treatments significantly inhibited the LPS-induced overproduction of NO, IL-6, and TNF-α (p < 0.05). BVEs also suppressed the LPS-induced phosphorylation of p65, IKKα, and IκBα. These findings revealed that volatile extracts from black raspberries, blueberries, and blackberries improve intestinal barrier dysfunction by enhancing intestinal epithelial monolayer integrity and exhibit intestinal anti-inflammatory effects by suppressing pro-inflammatory mediator and cytokines through modulating NF-κB signaling pathway. It suggests that the three berry volatile extracts have the potential as functional food components with gastrointestinal protective effects with anti-inflammatory properties.